The pain as non-motor complication of Parkinson's Disease - El dolor como complicación no motora de la enfermedad de Parkinson - Anelys Sánchez López; Arnoldo Padrón Sánchez; Dania Gutiérrez Fernández; Aracne Bernis Lastre; Ricardo Valdés Llerena (Publiediting, 2018)
Pain is a very common non-motor symptom in Parkinson's disease (PD), although undervalued. We analyzed the prevalence of pain, characteristics, associated factors and their impact on the quality of life and autonomy in a group of patients with PD. The objective is to characterize the incidence of pain as a non-motor complication of Parkinson's disease determining the characteristics and classification of pain in each case. It was demonstrated that there is a high prevalence of patients with PD who suffer of pain, as one of the non-motor complications of the disease and unfortunately this symptom is underdiagnosed and undertreated. We intend to expand the casuistry and propose a diagnostic evaluation of pain and draw a diagnostic and therapeutic strategy based on improving the quality of life of our patients.